The effect of the timing of exposure to Campylobacter jejuni on the gut microbiome and inflammatory responses of broiler chickens - Connerton, Phillippa L.; Richards, Philip J.; Lafontaine, Geraldine M.; O'Kane, Peter M.; Ghaffar, Nacheervan M.; Cummings, Nicola J; Smith, Darren L.; Fish, Neville M.; Connerton, Ian F. (BioMed Central, 2018)
Background Campylobacters are an unwelcome member of the poultry gut microbiota in terms of food safety. The objective of this study was to compare the microbiota, inflammatory responses, and zootechnical parameters of broiler chickens not exposed to Campylobacter jejuni with those exposed either early at 6 days old or at the age commercial broiler chicken flocks are frequently observed to become colonized at 20 days old. Results Birds infected with Campylobacter at 20 days became cecal colonized within 2 days of exposure, whereas birds infected at 6 days of age did not show complete colonization of the sample cohort until 9 days post-infection. All birds sampled thereafter were colonized until the end of the study at 35 days (mean 6.1 log10 CFU per g of cecal contents). The cecal microbiota of birds infected with Campylobacter were significantly different to age-matched non-infected controls at 2 days post-infection but generally the composition of the cecal microbiota were more affected by bird age as the time post infection increased. The effects of Campylobacter colonization on the cecal microbiota were associated with reductions in the relative abundance of OTUs within the taxonomic family Lactobacillaceae and the Clostridium cluster XIVa. Specific members of the Lachnospiraceae and Ruminococcaceae families exhibit transient shifts in microbial community populations dependent upon the age at which the birds become colonized by C. jejuni. Analysis of ileal and cecal chemokine/cytokine gene expression revealed increases in IL-6, IL-17A and Il-17F consistent with a Th17 response but the persistence of the response was dependent on the stage/time of C. jejuni colonization that coincide with significant reductions in the abundance of Clostridium cluster XIVa. Conclusions This study combines microbiome data, cytokine/chemokine gene expression with intestinal villus and crypt measurements to compare chickens colonized early or late in the rearing cycle to provide insights into the process and outcomes of Campylobacter colonization. Early colonization results in a transient growth rate reduction and pro-inflammatory response but persistent modification of the cecal microbiota. Late colonization produces pro-inflammatory responses with changes in the cecal microbiota that will endure in market ready chickens.